Support for the Systematic Study of Religion: A Response to Markus Davidsen - Sterken, Arjan (NTT, 2020)
Reacting positively to Markus Davidsen’s call for a Dutch programme of systematic study of religion, this response highlights certain points of discussion that should be considered moving forward. First of all, we should consider letting students get familiar with theories about religion earlier in the curriculum. Secondly, philological competences should not be placed above other methodological competences. Thirdly, our comparative methods should be informed by postmodernist critiques. Fourthly, we should be careful when applying cognitive theory by understanding its limitations. Finally, it remains unclear why methodological naturalism is the only way to move forward.